Release Pattern of Light Aromatic Hydrocarbons during the Biomass Roasting Process - Yaying Zhao; Yuqing Yan; Yuhang Jiang; Yang Cao; Zhuozhi Wang; Jiapeng Li; Chenshuai Yan; Danya Wang; Lu Yuan; Guangbo Zhao (Molecules, 2024)
Roasting is an important step in the pretreatment of biomass upgrading. Roasting can improve the fuel quality of biomass, reduce the O/C and H/C ratios in the biomass, and provide the biomass with a fuel quality comparable to that of lignite. Therefore, studying the structure and component evolution laws during biomass roasting treatment is important for the rational and efficient utilization of biomass. When the roasting temperature is 200–300 °C, the cellulose and hemicellulose in the biomass undergo a depolymerization reaction, releasing many monocyclic aromatic hydrocarbons with high reactivity. The proportion of monocyclic aromatic hydrocarbons in biomass roasting products can be effectively regulated by controlling the reaction temperature, residence time, catalyst, baking atmosphere, and other factors in the biomass roasting process. This paper focuses on the dissociation law of organic components in the pretreatment process of biomass roasting.